Artikel Review: Pengaruh Variasi Konsentrasi Bahan Pengikat Pada Formulasi Tablet Salut Serta Karakteristik Terhadap Sifat Fisik Sediaan - Marcelinda Krisdivayanti; Icasia Carolina Dewi; Laila Sabila Sindriyani; Ana Fatmah Azzahro; Nabyla Qutrun Nada; Alfan Hermawan; Dewi Rahmawati; Yani Ambari; Marthy Meliana Ariyanti Jalmav; Muhammad Fithrul Mubarak (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Coated tablets are compressed tablets that are coated with a mixture of various substances such as: resin, gum, fillers, sugar, plasticizers, polyols, coloring agents, and flavor enhancers in the active substance. The types of coated tablets that are developing are sugar-coated, thin-coated and enteric-coated tablets. One of the additional materials that plays an important role in making coated tablets is a binder. This review article aims to obtain information and examine what is a good concentration of binder to use in coated tablet formulations. Based on a literature study from several articles collected, it can be concluded that the lactose binder, porang tuber starch, and PVP in several coated tablet dosage formulations, these binders have no effect on the physical properties of the dosage form.